New findings of Cryptomarasmius (Physalacriaceae, Agaricales) from Jilin Province, China - Li, Siying; Bau, Tolgor (Phytotaxa, 2024)
We conducted a field investigation of marasmioid fungi in Jilin Province, China. Based on morphological and phylogenetic studies, seven specimens belonged to Cryptomarasmius (Physalacriaceae) were identified as three species. Phylogenetic analyses of ITS-nrLSU datasets conducted using Maximum Likelihood and Bayesian methods showed that C. changchunensis and C. aucubae are a new species and newly recorded species to China, respectively. Detailed descriptions and illustrations of the two species are provided in this study.